TRADISI MANYAMBAU MASYARAKAT KENEGERIAN KABUN KECAMATAN KABUN KABUPATEN ROKAN HULU - Rahmi, Nur; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The Villagers have a tradition that Kabun Jalang Manjalang and Manyambau. In this study the authors focus more discuss about manyambau, because so many have turned from activities such as the number of manyambau bearer jambau, clothes, fill in the jambau and the meaning of manyambau. The purpose of the research was in response to a wish expressed of a research. Then the researchers tried to put forward some of the goals of this research that he did, to find out how the value and function of the manyambau tradition anak kemenakan in the village of Kabun sub District of Rokan Hulu, to see how the patterns of behavior ninik mamak in maintaining tradition manyambau in the village of Kabun sub District of Rokan Hulu. In this study there are two sources of information needed by researchers that Key Informants and Respondents. As for the shifting of value and function manyambau for development of anak kemenakan caused by science and technology and the development of science and technology results in anak kemenakan less concerned with their traditions. And seeing these changes provide solutions to maintain ninik mamak this tradition which is attracting attention by giving anak kemenakan gifts of money to the bearer of the jambau and make a meeting with anak kemenakan every month to give you referrals to anak kemenakan about customs in the village including Kabun manyambau.Keywords: Change, Tradition, Manyambau